2016
DOI: 10.1136/annrheumdis-2016-eular.1431
|View full text |Cite
|
Sign up to set email alerts
|

AB1006 Anti-Citrullinated Peptide Antibodies and Rheumatoid Factor Testing Patterns among Patients with Rheumatoid Arthritis in The US: Table 1.

Abstract: BackgroundSerological markers have been investigated for the identification of RA. Current diagnostic criteria recommend conducting tests for anti-citrullinated peptide antibodies (ACPA) and rheumatoid factor (RF) prior to reaching the RA diagnosis. However, there is a lack of information about how these tests are utilized in a managed care setting.ObjectivesTo describe the frequency of ACPA/RF tests at the time of RA diagnosis and at follow-up, as well as to compare baseline characteristics between patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…[7][8][9][10] Our previous findings revealed that the majority of RA patients in an integrated health care delivery system received anti-CCP testing at the time of RA diagnosis. 11 The presence of a positive anti-CCP test has been associated with a more destructive course of disease, disease severity, by the KPSC Institutional Review Board; the requirement for written informed consent was waived due to the observational nature of the study.…”
mentioning
confidence: 99%
“…[7][8][9][10] Our previous findings revealed that the majority of RA patients in an integrated health care delivery system received anti-CCP testing at the time of RA diagnosis. 11 The presence of a positive anti-CCP test has been associated with a more destructive course of disease, disease severity, by the KPSC Institutional Review Board; the requirement for written informed consent was waived due to the observational nature of the study.…”
mentioning
confidence: 99%